Pemphigus vulgaris in a patient with arthritis and uveitis: successful treatment with immunosuppressive therapy and acyclovir. Issue 4 (18th February 2014) - Pranteda, G.; Carlesimo, M.; Bottoni, U.; Di Napoli, A.; Muscianese, M.; Pimpinelli, F.; Cordiali, P.; Laganà, B.; Pranteda, G.; Di Carlo, A.
Abstract A case of pemphigus vulgaris in a 41‐year‐old man with undifferentiated arthritis and uveitis is described. Histology of labial mucosa showed acantholytic, necrotic, and multinucleated giant keratinocytes having some nuclear inclusions suggestive of a virus infection. Specific serological tests revealed IgG positivity for HSV‐1, CMV, and EBV, while real‐time polymerase chain reaction assay from a biopsy of the mucosal lesion showed the presence of HSV‐1/2 DNA. Treatment with prednisone, methotrexate, and acyclovir induced the complete remission of mucosal and joint symptoms, which then relapsed after interruption of antiviral therapy or immunosuppressive therapy. Therefore, a combined treatment with low doses of prednisone, methotrexate, and acyclovir was restarted and during 18 months of follow‐up no recurrence was registered. Correlations between pemphigus and the herpes virus infection and also between autoimmune arthritis and herpetic agents have been well documented, but the exact role of the herpes virus in these disorders still needs further discussion. Our case strongly suggests that when autoimmune disorders do not respond to immunosuppressive agents, a viral infection should be suspected, researched, and treated.